ANALISIS SEKTOR UNGGULAN DALAM MENINGKATKAN PERTUMBUHAN EKONOMI DI KABUPATEN LAMONGAN - Achmad Dany Raihan; Joko Priyono (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
His study aims to identify leading sectors that can enhance economic growth in Lamongan Regency from 2019 to 2023. Leading sectors are crucial as understanding their strengths can significantly contribute to economic growth in a region, which is expected to have a positive impact on social indicators for the community. This is a quantitative research utilizing secondary data obtained from the Central Statistics Agency (Badan Pusat Statistik) of Lamongan Regency and East Java Province. The data used consists of panel data covering a time series spanning 5 years. The methods employed include Location Quotient (LQ) analysis, Shift Share (SS) analysis, and Klassen Typology. The research findings indicate that agriculture, forestry, and fisheries are the primary sectors contributing the most to the Gross Regional Domestic Product (GRDP). These findings serve as the basis for developing policies aimed at accelerating regional economic growth